2016
DOI: 10.3390/f7070135
|View full text |Cite
|
Sign up to set email alerts
|

Wood Density and Mechanical Properties of Pinus kesiya Royle ex Gordon in Malawi

Abstract: Successful development of an appropriate tree breeding strategy and wood utilization requires information on wood properties. This study was therefore conducted to assess wood density and mechanical properties of Pinus kesiya Royle ex Gordon grown in Malawi. Wood samples from six families of P. kesiya at the age of 30 years were used for the study. The estimated mean wood density, Modulus of Elasticity (MoE), Modulus of Rupture (MoR) and moisture content were 0.593˘0.001 g/cm 3 , 13.46˘0.07 GPa, 113.67˘0.57 MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 14 publications
5
28
0
1
Order By: Relevance
“…Wood sample processing and measurement was conducted as outlined by Missanjo and Matsumura [18]. Briefly, a total of 1080 wood specimens, measuring 20 mm × 20 mm × 320 mm, were collected from innerwood, middlewood and outerwood at 1.3 m, 3.3 m, 5.3 m and 7.3 m tree height.…”
Section: Wood Sample Processing and Measurementmentioning
confidence: 99%
“…Wood sample processing and measurement was conducted as outlined by Missanjo and Matsumura [18]. Briefly, a total of 1080 wood specimens, measuring 20 mm × 20 mm × 320 mm, were collected from innerwood, middlewood and outerwood at 1.3 m, 3.3 m, 5.3 m and 7.3 m tree height.…”
Section: Wood Sample Processing and Measurementmentioning
confidence: 99%
“…Sulaiman et al (2012) suggested that the new mechanical properties of compressed OPW was observed as the cellular structure of OPW was altered permanently during compression process. The higher bending strength recorded in waned sample could be attributed to its higher initial density after sawing as density is the most important parameter that affect the properties of the material (Missanjo and Matsumura, 2016). Reverse cant sawing pattern produced slabs with higher density in comparison with polygon sawing and therefore showed better properties.…”
Section: Dimensional Stabilitymentioning
confidence: 93%
“…The mean height, diameter at breast height (DBH), and volume of the trees expressed with standard deviations during sampling were 25.9 ± 2.8 m, 32.0 ± 3.9 cm and 0.989 ± 0.319 cm 3 , respectively. Wood sample processing and measurement was conducted as outlined by Missanjo and Matsumura [10]. Briefly, a total of 1080 wood specimens, measured 20 mm × 20 mm × 320 mm, were collected from innerwood, middlewood and outerwood at 1.3 m, 3.3 m, 5.3 m and 7.3 m of the stem height.…”
Section: Study Area Genetic Materials and Assessmentmentioning
confidence: 99%
“…It is mainly used for sawn timber production. Its morphology, uses and application in Malawi have been well explained by other researchers [9,10]. The breeding programme for this species in Malawi started in early 1970s with the aim of improving growth characteristics and tree stem form [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation